2020
DOI: 10.1038/s41598-020-79257-3
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of glass-ionomer cement containing ethanolic Brazilian pepper extract (Schinus terebinthifolius Raddi) fruits: chemical and biological assays

Abstract: Plants may contain beneficial or potentially dangerous substances to humans. This study aimed to prepare and evaluate a new drug delivery system based on a glass-ionomer-Brazilian pepper extract composite, to check for its activity against pathogenic microorganisms of the oral cavity, along with its in vitro biocompatibility. The ethanolic Brazilian pepper extract (BPE), the glass-ionomer cement (GIC) and the composite GIC-BPE were characterized by scanning electron microscopy, attenuated total reflectance Fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 78 publications
0
3
0
4
Order By: Relevance
“…Green chemistry route is followed in the synthesis of polyalkenoic acid since its Review Materials Advances invention. Recent studies showed that researchers around the globe have claimed green synthesis routes for GIC using different additives such as carbohydrates, 70,71 organic acids [72][73][74] and other plant-based [75][76][77] materials to enhance its properties. For example, Dola Sundeep et al investigated the effect of silver nanoparticles synthesized from the Mangifera indica leaves and studied the antimicrobial effect against Escherichia coli and Staphylococcus aureus at different concentrations in GIC.…”
Section: Green Chemistry Route For the Synthesis Of Polyalkenoic Acidmentioning
confidence: 99%
“…Green chemistry route is followed in the synthesis of polyalkenoic acid since its Review Materials Advances invention. Recent studies showed that researchers around the globe have claimed green synthesis routes for GIC using different additives such as carbohydrates, 70,71 organic acids [72][73][74] and other plant-based [75][76][77] materials to enhance its properties. For example, Dola Sundeep et al investigated the effect of silver nanoparticles synthesized from the Mangifera indica leaves and studied the antimicrobial effect against Escherichia coli and Staphylococcus aureus at different concentrations in GIC.…”
Section: Green Chemistry Route For the Synthesis Of Polyalkenoic Acidmentioning
confidence: 99%
“…MRC-5 cells are commonly used to evaluate the safety profile of both natural and synthetic compounds [44,45]. This cell line is often featured in scientific investigations and laboratory experiments that aim to scrutinize various cellular processes, responses to external stimuli, and intricate cellular interactions.…”
Section: Cytotoxicity Assaymentioning
confidence: 99%
“…Os dados de interesse foram selecionados, plotados em planilhas, gráficos e diagramas de fluxo de pesquisa. com produtos derivados da pimenta rosa, propondo, inclusive, formulações farmacêuticas para saúde a base de pimenta rosa [17][18][19] ; além da atividade biológica de extratos obtidos do resíduo agroindustrial da pimenta rosa [20] ; novas atividades biológicas in vitro e in vivo de extratos de pimenta rosa e compostos isolados [5,6,21,22] ; estudo em Aromoterapia com óleo essencial da pimenta rosa [23] ; prospecção e potencial biotecnológico da espécie Schinus terebinthifolius Raddi, bem como a correlação de bioativos e seus potenciais benefícios para a saúde humana [16,[24][25][26][27] ; e, por último, um trabalho de Análise Cienciométrica cujos resultados trouxeram um panorama geral sobre o norteamento de pesquisas científicas mundiais com a espécie Schinus terebinthifolius Raddi nos últimos anos, de 2001 até maio de 2021 [14] .…”
Section: Metodologiaunclassified